Trauma Sex: A Queercrip Erotic - J. Logan Smilges (Disability Studies Quarterly, 2020)
Sometimes sex is really fucking hard. Pun intended. This essay explores the role of trauma in sex, arguing that experiences of trauma can reconstitute the erotic in ways that are incompatible with prevailing discourses on queerness, consent, and sexual violence. "Trauma sex" is a way of capturing the queer and crip flavors of this erotic reconstitution by demonstrating how many of us experience sex, sexuality, and desire in ways that go unremarked on by disability and queer studies, independently. Grounded in "conscientious intimacy," trauma sex brings together disability and queer studies to call for an opening up of desire, a radical expansion of what we acknowledge as sex, sexual, and sexy, by attending to the troubling absence of disability from queer theory, of trauma from disability studies, and of the inadequate attention to race and processes of racialization in both fields. Sex and trauma are complicated, this essay suggests, so our conversations about them should be too.
Keywords: trauma; sex; queer; queercrip